Alternative synthesis of the CNS stimulant Prolintane - Mujahid, M.; Korpe, G. V.; Deshmukh, S. P.; Bhadange, S. G.; Muthukrishnan, M. (Arkivoc, 2019)
An alternative synthesis of prolintane, a CNS stimulant, is reported using commercially available allyl benzene in good overall yield (32.3%). The key transformations include epoxidation, Grignard reaction, Mitsunobu and reduction protocols.

Efficient and cost effective synthesis of acetamides catalyzed by calcium chloride - Sangole, M. T.; Thorat, S. M.; Shirsath, S.; Deshmukh, S. P.; Muthukrishnan, M.; Mujahid, M. (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2019)
CaCl2 has been found to be an efficient and cost effective catalyst for the rapid synthesis of acetamides in high yields. The use of stoichiometric quantities of acetic anhydride under solvent free conditions without any additional chromatographic purifications makes this protocol a safe alternative to the existing methods.
Keywords: Acetamide; acetylation; Acylation; Amine; CaCl2